California Condor Associated with Spruce-jack Pine Woodland in the Late Pleistocene of New York - D. W. Steadman; N. G., Miller (Quaternary Research, 1987)
A humerus, coracoid, and pedal phalanx of the California Condor, Gymnogyps californianus, were recovered from the Hiscock Site in western New York, in an inorganic stratum containing wood that is 11,000 radiocarbon years old. Associated vertebrates include mastodont, wapiti, and caribou. Pollen and plant macrofossils from the sediments indicate a spruce-jack pine woodland and a local, herb-dominated wetland community. Historic records (all from western North America) and previous late Pleistocene fossils of the California Condor are associated mainly with warm-temperate climates and floras. The New York fossils show that this bird was able to live in a colder climate and in a boreal, coniferous setting at a time when appropriate food (large mammal carrion) was available. The California Condor, which survives only in captivity, has suffered a greater reduction in geographical range than previously suspected. Much of this reduction in range probably occurred ca. 11,000 yr B.P. when the extinction many North American large mammals resulted in severely reduced availability of food for the California Condor and other large scavenging birds.
Keywords: biology paleontology